2020
DOI: 10.1128/jvi.01508-19
|View full text |Cite
|
Sign up to set email alerts
|

LANA and hnRNP A1 Regulate the Translation of LANA mRNA through G-Quadruplexes

Abstract: During the latent phase, Kaposi’s sarcoma-associated herpes virus (KSHV) maintains itself inside the host by escaping the host immune surveillance mechanism through restricted protein expression. Latency-associated nuclear antigen (LANA), the most abundantly expressed protein, is essential for viral persistence, as it plays important roles in latent viral DNA replication and efficient segregation of the viral genome to the daughter cells following cell division. KSHV evades immune detection by maintaining the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 57 publications
3
53
1
Order By: Relevance
“…Interestingly, reduced translation has been found to be strictly related to reduction of antigen presentation, one of the main mechanisms adopted by LANA1 to promote immune evasion. 35 Altogether, these data confirm that G4s are key regulatory element in the regulation of host-pathogen interaction in the Herpesviridae family and support the feasible exploitation of these structures as innovative pharmacological targets in the antiherpetic therapy.…”
Section: Kaposi's Sarcoma-associated Herpesvirussupporting
confidence: 60%
“…Interestingly, reduced translation has been found to be strictly related to reduction of antigen presentation, one of the main mechanisms adopted by LANA1 to promote immune evasion. 35 Altogether, these data confirm that G4s are key regulatory element in the regulation of host-pathogen interaction in the Herpesviridae family and support the feasible exploitation of these structures as innovative pharmacological targets in the antiherpetic therapy.…”
Section: Kaposi's Sarcoma-associated Herpesvirussupporting
confidence: 60%
“…The first exploits the ability of RG4s in both EBNA1 and LANA mRNAs coding sequences to inhibit the translation of these proteins. The structure-immune function relationship was demonstrated by modulating RG4s folding, which then resulted in the altered expression of the viral proteins and, in turn, in modified antigen presentation [85][86][87]. Although the molecular mechanism awaits further investigation, host cell protein factors (hnRNP A1 and nucleolin for LANA and EBNA1 mRNAs, respectively) take part in this regulation by interacting with RG4 structures [86,87].…”
Section: Rg4 Misregulation In Disease: Focus On Immune Evasionmentioning
confidence: 99%
“…The structure-immune function relationship was demonstrated by modulating RG4s folding, which then resulted in the altered expression of the viral proteins and, in turn, in modified antigen presentation [85][86][87]. Although the molecular mechanism awaits further investigation, host cell protein factors (hnRNP A1 and nucleolin for LANA and EBNA1 mRNAs, respectively) take part in this regulation by interacting with RG4 structures [86,87]. This is consistent with the observation that terms associated with viral infection are over-represented in cellular RG4-protein interaction data sets [5,18,19,87].…”
Section: Rg4 Misregulation In Disease: Focus On Immune Evasionmentioning
confidence: 99%
“…G4s have gained some notice for their control over DNA/RNA metabolism. DsDNA viruses have been found to be particularly enriched with putative G4-forming sequences (PQS) [51], and KSHV LANA gene was found to form G4s within its own mRNA [52]. It was demonstrated that LANA protein itself binds to the G4 regions of its own mRNA to prohibit its export to the cytoplasm and thus help control its expression.…”
Section: Nuclear Exportmentioning
confidence: 99%
“…LANA has been shown to modulate antigen presentation by interacting with components of the antigen presentation [66,67]. G4s are now thought to be another way KSHV dampens immune responses by reducing translation of LANA1 and, therefore, this reduces antigen presentation [52]. Together it can be seen that G4s are being used as a regulatory element between host and virus.…”
Section: Mrna Translationmentioning
confidence: 99%